OFR-103(2)-75 Circuit Breaker Development And Application - USBM Contract Phase II Report - Section 1. Program Objectives And Results - 1.1 Summary - D. A. Paice (The National Institute for Occupational Safety and Health (NIOSH), 2012)
Under the first phase of this contract as reported in the Phase I report it was determined that certain types of commercially available molded case breakers are capable of interrupting mine dc power supplies of nominally 300 volts or 600 volts rating. These circuit breakers incorporate conventional overcurrent trip units but also can be operated by means of low power signals fed to a shunt trip coil. Further development in the Phase I program produced a means whereby a discriminating circuit breaker detector unit could sense the presence of illegitimate loads on the dc electrical system and cause the circuit breaker to trip. The detector unit operated by detecting the presence of 3000 Hz currents which were generated in the illegitimate loads by means of a 12 volt, 3000 Hz signal applied to the dc system. Further development of the program has continued in Phase II with the aim of verifying the practicability of the complete discriminating circuit breaker concept and developing other types of equipments required to implement a system. These other equipments include electronic means for raising the apparent impedance of high power legitimate loads and static filters for smaller loads. The results of laboratory work and limited underground tests have been successful. This report describes the system and the tests that have been conducted on the various equipments that comprise the complete Discriminating Circuit Breaker Concept.